You heard it first on Radio Spore ! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Benjamin Dembele, President of the Urban Group for Poultry and Farm Development in Bonoua, Côte d'Ivoire, tells us 'how our fifteen farms get together to get and discuss Spore. When we go back to town, we run a reading club to reach out to more...